Introduction - Simplice Asongu (African Governance and Development Institute (AGDI), 2018)
This special section aims to advance scholarship on well-being and happiness in Africa. The section covers theoretical, conceptual and empirical contributions which address relevant areas that enhance extant knowledge on linkages between poverty, happiness and well-being in Africa.
Keywords: D31; I10; I32; K40; O55; 330; Economic Growth; Inclusive Development; Well-Being